Applying adherent DBT Principles to treatment in a partial hospital setting: An analysis over 5‐years of outcomes from intake to discharge. Issue 11 (1st June 2021) - Lothes, John E.; McCool, Matison W.; Mochrie, Kirk D.; Guendner, Eric; St. John, Jane
Abstract: Objectives: A small number of studies to date have examined Partial Hospital (PH) that utilize a Dialectical Behavior Therapy (DBT) model. Preliminary findings suggest DBT PH programs can be effective in various symptom reduction. Methods: This study examined clinically relevant outcomes and included a heterogeneous clinical sample over a five‐year period. Specifically, the present study assessed pre–post data to examine changes in symptoms of depression, anxiety, hopelessness, and overall degree of suffering from intake to discharge in a DBT PH. Results: Findings showed symptom reduction from intake to discharge for depression, anxiety, hopelessness, and suffering for all 5 years. This DBT PH program was successful at reducing various symptoms in a sample of psychiatric patients. Conclusion: Clinicians might consider the advantages of placing patients in PH programs versus an inpatient stay or consider utilizing DBT‐informed PH programs after an inpatient hospitalization as a form of step‐down care.